Comparison of single shot caudal Ropivacaine and Bupivacaine in paediatric patients undergoing herniotomy - Ravi, Rishabh; Shakya, Bigen Man; Shrestha, Anil; Koirala, Megha (Grande Medical Journal, 2019)
Background: Inguinal hernia repair is a common surgical procedure in children. Caudal block is an appropriate technique for the treatment of post operative pain in children undergoing herniotomy. This study compared the effects of Ropivacaine and Bupivacaine in caudal block in children undergoing herniotomy. Methodology: A total of 74 patients between 5-16 yrs undergoing herniotomy were randomized in two groups. In Group B, 0.75ml/kg of 0.25% caudal Bupivacaine was administered whereas Group R received 0.75 ml/kg of 0.25% caudal Ropivacaine. Pain score was assessed using Wong Baker pain scale in post operative period and motor power was assessed using modified Bromage scale till 6 hours. Results: The mean duration of post operative analgesia was found to be 253.51 ± 11.48 minutes in Bupivacaine and 258.1 ± 12.10 minutes in Ropivacaine group. The median duration of motor block was 180 (Q1 60- Q3 180) minutes in Bupivacaine and 30 (Q1 22.5- Q3 45) minutes in Ropivacaine group which was statistically significant. There was complete recovery of motor block by 2 hour in Ropivacaine and by 4 hour in Bupivacaine group. (p value< 0.001). Conclusion: From the current study, it is concluded that caudal Ropivacaine at 0.25% concentration and 0.75ml/ kg provides similar duration of post operative analgesia with less motor block in comparison to Bupivacaine.